BAGAIMANA PERLINDUNGAN HUKUM INVESTOR PASAR MODAL DALAM UU NO 8 TAHUN 1995 - Arka Candias Hermawan; Gunardi Lie (Jurnal Riset Multidisiplin Edukasi, 2025)
The capital market serves a pivotal function in the economy by facilitating the acquisition of long-term capital and acting as a mechanism for financial intermediation.  Investment operations in the capital market are susceptible to many hazards, including fraudulent tactics, price manipulation, and insider trading, which can adversely affect investors.  Consequently, regulatory safeguards for investors are essential for preserving public confidence and ensuring the viability of a robust capital market.  This study intends to examine the legal protections delineated in Law Number 8 of 1995 regarding Capital Markets (UUPM) and evaluate the efficacy of its implementation.  The research employs a normative legal methodology utilising statutory, conceptual, case-based, and comparative approaches.  The findings demonstrate that legal protection inside the UUPM is enforced via two primary pillars. The preventive pillar is realized through the principle of disclosure, both in prospectuses and in periodic and incidental reports, to reduce information asymmetry. The repressive pillar is enforced through prohibitions on fraud, market manipulation, and insider trading, supported by administrative, criminal, and civil sanctions. The combination of these two pillars creates a balance between prevention and enforcement, thereby fostering an orderly, fair, and efficient capital market. Nevertheless, the effectiveness of legal protection is highly dependent on implementation quality, particularly regarding the standards of materiality and timeliness of disclosure, the speed and certainty of law enforcement, as well as the integrity of corporate governance and supporting professions. Hence, strengthening supervision, improving investor education, and updating regulations to adapt to technological developments and market dynamics are essential to achieve sustainable investor protection.